Breathable Films with Self-Cleaning and Antibacterial Surfaces Based on TiO2-Functionalized PET Membranes - Olga Alisiyonak; Anna Lavitskaya; Liudmila Khoroshko; Artem L. Kozlovskiy; Maxim Zdorovets; Ilya Korolkov; Maryia Yauseichuk; Egor Kaniukov; Alena Shumskaya (Membranes, 2023)
A promising approach that uses the sol–gel method to manufacture new breathable active films with self-cleaning and antibacterial surfaces is based on the PET membranes obtained via ion track technology with a pore density of 10–7 cm−2 and a pore diameter of about 500 ± 15 nm, coated with a layer of TiO2 anatase, with a thickness of up to 80 nm. The formation of the photocatalytically active TiO2 anatase phase was confirmed using Raman analysis. Coating the PET membrane with a layer of TiO2 increased the hydrophobicity of the system (CA increased from 64.2 to 92.4, and the antibacterial activity was evaluated using Escherichia coli and Staphylococcus aureus bacteria with the logarithmic reduction factors of 3.34 and 4.24, respectively).